Noah and The Great Flood - Penny Frank; Tony Morris (UK USA Lion Publishing, 1986)
Retells the Old Testament story of Noah, the one man with whom God was pleased when he decided to wipe out the world's population with a great flood.
color illustrations ; Australia
GB8538472 bnb
Keywords: Theology: Miscellaneous (3GddGghJ(B: (3eJaQbGJs; Noah's ark -- Juvenile literature; Theology; Bible stories, English -- Genesis